Analisis Transformasi Wilayah Peri-Urban pada Aspek Fisik dan Sosial Ekonomi (Kecamatan Kartasura) - Kurnianingsih, Nela Agustin; Rudiarto, Iwan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
The development of a peri-urban zone, which appears as a transitional zone from rural to urban characteristics urged by the external development of an urban region, is in fact able to contribute different characteristics among parts of the region, especially on its physical and socio-economic aspects, is like in Kartasura Subdistrict. Kartasura Subdistrict, that shows both of urban development characteristics influenced by Surakarta City and rural existency affected by its rural areas, actually has a greatly land-changing history between 1997â€“2002 where the changes only started at a few spots. Therefore, it is believed that there is aÂ  zone transformation process that happens periodically and has changed the condition and pattern of transformation rate. Based on the research, it has shown that during the transformation processes between 2002 and 2012, the Peri-Urban Zones of Kartasura Subdistrict have been developing into urban zones, shown by the activity displacement from agriculture to non-agriculture and peoples activities on social and economic sectors, also this research has shown that Kartasura had the uneven spread of transformation rates.